Can Thymic Tissue Induce Tolerance to Kidney Allografts? - Shakeri, Saeed; Aminsharifi, Alireza; Khezri, Abdolaziz; Monabbati, Ahmad; Tanideh, Nader (Urology Journal, 2009)
<!--[if gte mso 9]> Normal 0 false false false EN-US X-NONE AR-SA MicrosoftInternetExplorer4 <![endif]--><!--[if gte mso 9]> <![endif]--> <!-- /* Font Definitions */ @font-face {font-family:"Cambria Math"; panose-1:2 4 5 3 5 4 6 3 2 4; mso-font-charset:0; mso-generic-font-family:roman; mso-font-pitch:variable; mso-font-signature:-1610611985 1107304683 0 0 159 0;} /* Style Definitions */ p.MsoNormal, li.MsoNormal, div.MsoNormal {mso-style-unhide:no; mso-style-qformat:yes; mso-style-parent:""; margin:0cm; margin-bottom:.0001pt; text-align:right; mso-pagination:widow-orphan; direction:rtl; unicode-bidi:embed; font-size:12.0pt; font-family:"Times New Roman","serif"; mso-fareast-font-family:"Times New Roman";} p.MsoBodyText, li.MsoBodyText, div.MsoBodyText {mso-style-unhide:no; mso-style-link:"Body Text Char"; margin:0cm; margin-bottom:.0001pt; text-align:center; line-height:150%; mso-pagination:widow-orphan; font-size:12.0pt; font-family:"Times New Roman","serif"; mso-fareast-font-family:"Times New Roman"; font-style:italic;} span.BodyTextChar {mso-style-name:"Body Text Char"; mso-style-unhide:no; mso-style-locked:yes; mso-style-link:"Body Text"; mso-ansi-font-size:12.0pt; mso-bidi-font-size:12.0pt; font-style:italic;} .MsoChpDefault {mso-style-type:export-only; mso-default-props:yes; font-size:10.0pt; mso-ansi-font-size:10.0pt; mso-bidi-font-size:10.0pt;} @page Section1 {size:612.0pt 792.0pt; margin:72.0pt 72.0pt 72.0pt 72.0pt; mso-header-margin:36.0pt; mso-footer-margin:36.0pt; mso-paper-source:0;} div.Section1 {page:Section1;} --> <!--[if gte mso 10]> <![endif]--> Introduction: The aim of this study was to investigate the beneficial effect of donor thymic tissue to induce tolerance in thymokidney allografts, transplanted to thymectomized cross-bred canines. Materials and Methods: Seven pairs of transplant donors and recipients were selected from 3- to 4-month-old cross-bred canines with major histocompatibility complex (MHC) mismatches. Recipients underwent partial thymectomy 4 weeks before transplantation and received an autologous thymic graft under the renal capsule, which had been engrafted in the donors 3 months before transplantation (thymokidney). Successful engraftment with evidence of thymocyte development in the donors was determined by gross and histologic examination at the time of transplantation. Biopsy specimens were obtained at the transplant day and 3 months after transplantation and were studied histologically for evidence of hyperacute or acute rejection. Results: At 90 days after the operation, all 7 juvenile thymic grafts had developed with normal thymic structure under the renal capsule. Hyperacute rejection was not observed in allografts, and all of them were functioning until the end of follow-up; however, all of the allografts showed acute cell-mediated rejection 3 months after transplantation. Conclusion: No tolerance was induced by vascularized donor thymokidneys in MHC-mismatched canines. The advantages of tolerance over chronic immunosuppression are so great that a potentially tolerogenic approach such as thymic transplantation would seem worthy of further investigations on large animal models. To evaluate the beneficial effects of thymic tissue in tolerance induction, utilizing a short course, low-dose adjuvant immunosuppressant to this regimen and/or application of in-bred MHC-matched canines is suggested.